Pathways linking mental health literacy to professional help‐seeking intentions in Korean college students - Kim, Eun Joo; Yu, Jung Hee; Kim, Eun Young (Journal of psychiatric and mental health nursing, 2020)
Accessible summary What is known on the subject? People in their twenties, including college students, experience a high level of stress and prevalence of related mental health problems including depression, anxiety and alcohol addiction, but they are the least likely age group in Korea to utilize professional help for mental health issues. Mental health literacy (MHL) refers to the knowledge and abilities necessary for maintaining mental health and preventing mental health problems. MHL also plays an important role in help‐seeking for mental health issues. Therefore, studying MHL and other variables related to help‐seeking is likely to enhance our overall understanding of students’ mental health. What this study adds to existing knowledge? Although there have been some studies of college students’ MHL in Korea, this is the first study to identify the paths and relationships between MHL and help‐seeking intentions in Korean college students. Additionally, this study examined the mediating role of stigma in the relationship between MHL and attitudes toward help‐seeking. The findings of this study suggest that MHL promotion can have a positive impact on the mental health of Korean college students by improving their attitudes toward help‐seeking and increasing their help‐seeking intentions. This study supports the idea that increased social support among Korean college students may reduce stigma and facilitate their seeking of professional help. The paths and relationships found in the present study provide evidence that a nursing intervention on‐campus that improves students’ MHL and reduces stigma may facilitate more effective use of help‐seeking services among college students. What are the implications for practice? MHL plays a significant role in how college students manage their mental health and the likelihood that they will seek professional help for mental health issues. Increasing MHL reduces mental health‐related stigma and promotes positive attitudes toward help‐seeking. A mental health nursing intervention that includes MHL improvement strategies would likely enhance students’ utilization of mental health services on campus. Although students’ MHL is improved by existing campus programmes and educational efforts to raise awareness of mental health, interventions should also address campus culture and stigma to facilitate mental health help‐seeking. Ultimately, enhancing MHL will contribute to the prevention of mental health problems and protect the deterioration of mental health among college students. Introduction There is a high prevalence of mental health problems among college students in Korea. Although the usage rate for mental health services among Korean college students was not reported, it is known that the usage rate for Koreans is low compared to that in the United States. Aim To explore the relationships linking mental health literacy (MHL) to intentions of help‐seeking in a sample of Korean college students. Method Using a cross‐sectional study, data from 200 participants were analysed using a structural equation modelling approach. Results Mental health literacy had both direct and indirect effects on attitudes toward help‐seeking and an indirect effect on attitudes toward help‐seeking through stigma. The direct effect of MHL on attitudes toward help‐seeking was fully mediated by stigma. Discussion Mental health nursing professionals have a responsibility and a challenge to enhance MHL in college students through individual or group interventions. Implications for practice MHL plays a significant role in individuals’ willingness to seek professional help when in need of mental health care. Thus, mental health nursing interventions that include MHL improvement strategies would favourably enhance students’ use of adequate sources of care and contribute to the prevention of mental health problems in college students.